An investigation of Polyether Imide (PEI) toughening of carbon fibre-reinforced Polyether Ether Ketone (PEEK) laminates. (15th December 2021) - McLaughlin, John W.; Tobin, Emma; O'Higgins, Ronan M.
Graphical abstract: Highlights: PEI film inclusions improve the Mode I and Mode II interlaminar toughness performance of CF/PEEK laminates. CF/PEEK laminates toughened with PEI film at delamination susceptible ply interfaces exhibited superior impact performance relative to baseline CF/PEEK laminates. PEI film toughened CF/PEEK laminates exhibited a smaller impact damage footprint relative to baseline CF/PEEK laminates. Unlike thermoset based composite laminates, all CF/PEEK and PEI toughened CF/PEEK laminates tested exhibited impact damage on the impact surface. This is a useful attribute in aerospace structures, where barely visible impact damage (BVID) is a concern for flight safety. Abstract: Current thermoset composite material systems have relatively low interlaminar fracture toughness, leaving them vulnerable to impact damage. While thermoplastic based systems are considered to be tougher, toughness levels can be dependent on processing parameters. In this study, Polyether imide (PEI) film layers were added to carbon fibre-reinforced Polyether ether ketone (CF/PEEK) laminate layups prior to consolidation to enhance the interlaminar toughness at key ply interfaces. It was found that the addition of the PEI film improves the Mode I and Mode II interlaminar toughness of the laminate. Low-velocity impact tests were performed on the PEI toughened CF/PEEK laminates, as well as a baseline CF/PEEK laminate and a CF/PEEK laminate with PEEK film inserts, for direct laminate thickness comparison. For low energy impacts (10 J), associated with tool drop events, it was found that the PEI toughened panel performed best. However, the performance difference decreased as the impact energy increased. Ultrasonic scans indicated that PEI toughened CF/PEEK laminates exhibited a smaller damage footprint. Compression after impact (CAI) and Combined Loading Compression (CLC) tests revealed that although the PEI inserts reduce the laminate undamaged compressive strength, they exhibited higher relative residual strengths compared to the other laminates tested.